Strategic Design of Synthetic Consortium with Embedded Wastewater Treatment Potential: Deciphering the Competence of Isolates from Diverse Microbiome - Dahiya, Shikha; Venkata Mohan, S. (Frontiers in Environmental Science, 2016)
Microorganisms plays vital role in efficient biological treatment. Supplementation of external microorganisms with high degradation rates can enhance the process efficiency significantly. Potential strains were isolated from long term wastewater treating reactors and identified using phylogenetic analysis of 16S rRNA gene fragments with the nearest neighbours extracted during BLAST search. Later the study was designed in two phases which revealed interesting findings. Phase I evaluates the potential of isolated strains viz., Pseudomonas otitidis, Bacillus firmus, Bacillus subtilis and Bacillus circulans for their individual ability in terms of COD and nutrients removal. Bacillus circulans showed highest carbon (COD) removal (70%; 0.56 kg CODR/m3-day), while maximum nutrients removal (nitrate, 81%; phosphates, 90%) was observed with Bacillus subtilis. B. firmus showed maximum volatile fatty acid (VFA) production. Based on Phase I results, four synthetic consortia were designed in phase II with diverse combination of isolates and evaluated for its remediation efficiencies. Consortium 4 (P. otitidis, B. subtilis and B. firmus) illustrated higher treatment potential [COD, 86%; SDR (cum): 0.64 kg CODR/m3-day; Nitrates, 87%; Phosphates, 97%]. The exploitation of such explicit consortia can overcome the inefficiencies pre-existing with the biological wastewater treatment plants by acting as prospective candidates for bio-augmenting the native microflora. This communication illustrated development of the efficient consortia using lab isolated strains to improve the performance of wastewater treatment.